2006
DOI: 10.1088/0953-8984/18/31/028
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional study of oxygen vacancies in monoclinic tungsten oxide

Abstract: A detailed study of the formation of neutral oxygen vacancies in monoclinic tungsten oxide (WO 3 ) is performed within the framework of the self-consistent first-principles SIESTA method. This work reveals that the neutral oxygen vacancies are anisotropic with a strong correlation to the structural anisotropy of the WO 3 monoclinic room temperature phase. We show that most of the structural relaxation around the vacancies occurs along a single straight line of W-O-W bonds and that the lowest energy corresponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 45 publications
8
33
0
Order By: Relevance
“…7 in the range from −3 to 5 eV. Moreover, the character of the total and partial DOS looks similar to those obtained for different phases of WO 3 and the Magnéli phases 17, 18. The similar partial DOS has been observed in isostructural monoclinic MoO 2 2, however, in MoO 2 the 4d e g states of Mo are practically absent at the Fermi level while in WO 2 their values are comparable to the t 2g states.…”
Section: Resultssupporting
confidence: 81%
“…7 in the range from −3 to 5 eV. Moreover, the character of the total and partial DOS looks similar to those obtained for different phases of WO 3 and the Magnéli phases 17, 18. The similar partial DOS has been observed in isostructural monoclinic MoO 2 2, however, in MoO 2 the 4d e g states of Mo are practically absent at the Fermi level while in WO 2 their values are comparable to the t 2g states.…”
Section: Resultssupporting
confidence: 81%
“…The oxygen vacancy was acquired by removing a single oxygen atom from the lateral surface layer of nanowire. Experimentally, the general diameter of as-synthesized single tungsten oxide nanowire is about several nanometers and the minimum value ever reported is 1 nm [19][20][21] [22] demonstrated that there exist three non-equivalent oxygens in the monoclinic phase of WO 3 . For the 1D nanowire constructed from the monoclinic WO 3 supercell, the three non-equivalent oxygens on the lateral surface are shown in Fig.1(a) After removal of O a , O b or O c , the formed neutral oxygen vacancies were respectively denoted as V a , V b and V c .…”
Section: Modeling Systemmentioning
confidence: 99%
“…77 However, the microscopic origin of this effect, which is intimately connected with the typical blue coloration of WO 3−x films, 78,79 has been longly debated, and several models have been put forward for rationalizing experimental observations. 77,80,81 On the theory side, a few first-principle investigations have been performed on O-deficient RT monoclinic WO 3 , [82][83][84] but among them only one 85 employed state-of-the-art methods yielding a correct description of the bulk electronic structure. The latter study of Wang et al, 85 revealed a delicate interplay between the concentration of O vacancies and the metallic or insulating nature of WO 3−x .…”
Section: B Womentioning
confidence: 99%